Error Analysis of Libyan Students’ Use of Derivational Morphemes - Alareefi, Emran Ali; Linggar Bharati, Anggani; Rozi, Fahrur (Universitas Negeri Semarang, 2021)
Word formation occurs when we want to form new meaning, word class, and grammatical need. Morpheme is defined as the smallest meaningful unit of a language. This study to purpose to explain the errors that Libyan students made in using derivational morphemes, to explain why they make such errors and to find the solutions to overcome these errors. Research design in this study is qualitative research. Data in the form of quotes from documents, field notes, and interviews or excerpts from videotapes, audiotapes, or electronic communications are used to present the findings of the study. Based on the findings and discussion, the conclusion of this research as follows: The errors made by Libyan students in Semarang city in using derivational morphemes is varied from one student to another student, from the omission, addition, misordering and misformation, about the prefix and suffix. The contribution made to this study is by knowing the number of errors that occur in Libyans in English.